Gorlin Goltz syndrome: a rare case report - Jain, Nitisha A.; Rathod, Vasantkumar J.; Gandhi, Mily S.; Ghai, Anshul P. (International Journal of Research in Medical Sciences, 2020)
Gorlin-Goltz syndrome is uncommon multisystemic disease with an autosomal dominant trait, with complete penetrance and variable expressivity, though sporadic cases have been described. We report a case of 18 years old male patient having features of Gorlin Goltz syndrome. Gorlin-Goltz syndrome is characterized by multiple basal cell nevi or carcinomas, odontogenic keratocysts, palmar and/or plantar pits, calcification of the falx cerebri, and is associated with internal malignancies. It is important to know the major and minor criteria for the diagnosis and early preventive treatment of this syndrome.